The Expression Of Command Used In Tintin Comic Manuscript: A Pragmatic Study - Parbaningrum, Devi (2012)
The aim of this study is to describe the pragmalinguistic forms, the speaker intentions, and the politeness strategy of commanding used in Tintin comic manuscript volume 1 Tintin in the Congo by Herge 2007. This study uses descriptive qualitative method. The data were the written text of commanding utterance used in Tintin comic volume 1 especially Tintin in the Congo by Herge 2007. The data of pragmalinguitic forms were analyzed by Marcella Frank, the intentions were analyzed by Searle's theory, and the politeness strategies were analyzed by Brown and Levinson. The research finding showed that there are two kinds of directive utterance: other-directed command and self-directed command used in Tintin comic. The linguitics form of them are declarative, positive imperative, negative imperative, imperative using Let's, interrogative, and combination. The intentions of them are assuring, asking a caution, asking a help, asking to take a rest, asking to pay for attention, asking to be in focus, arranging strategy, continuing adventure, extracting information, explaining, getting angry, motivating, persuading, permitting, prohibiting, to be in a hurry, resolving peacefully, warning, asking to be in focus and worrying. As for politeness strategy, the other-directed command uses both bald-on record and positive politeness, and the self-directed command only uses bald-on record.